Drama Ilahi: Sebuah Upaya dalam Membaca Kronologi Wahyu Alquran - Ikhwan, Munirul (Department of Qur'an dan Hadith Faculty of Ushuluddin and Philosophy UIN Sunan Ampel Surabaya, 2020)
Abstract: The chronology of revelation is one of the most complicated topics in Qur’anic studies because the Qur’an at its initial emergence did not appear as a neatly arranged codex, rather as a series of reflections on the ‘acts of God’ in a particular setting of human history responding various socio-religious issues. Departing from some previous studies, this article examines the chronology of revelation by situating the Qur’an within the historical context of the Prophet Muhammad’s career. This study takes a different emphasis from existing chronological theories which primarily rely on the analysis of the linguistic styles of the Qur’an in their relation to the psychology of the Prophet, or from those which are built on the sequence of religious ideas. By revisiting the existing chronological theories, this study argues that any effort to rebuild the chronology of revelation must be primarily based on the historical formation of the Qur’an’s dialectic with its first audience, to which analysis on its linguistic styles can support. This study sees the chronology of revelation as a “divine drama” which reflects dialectical communication between various actors summarized in a text which is later believed to be the word of God. Thus, this study emphasizes that the basis of the chronology of revelation is a series of events during the formation of Islam whereas the analysis on the linguistic styles of the Qur’an plays a complementary role. Abstrak: Kronologi wahyu adalah salah satu topik paling rumit dalam studi Alquran, karena Alquran pada awal kemunculannya tidak berwujud mushaf yang tertata rapi, namun muncul dari rangkaian refleksi ‘tindakan Tuhan’ dalam latar kesejarahan tertentu manusia yang merespon beragam isu sosial keagamaan. Bertolak dari studi-studi terdahulu, artikel ini mengulas kronologi wahyu dengan menempatkan Alquran dalam konteks sejarah karir Nabi Muhammad. Studi ini mengambil penekanan yang berbeda dari teori kronologi yang ada yang utamanya bertumpu pada analisis gaya bahasa Alquran dalam kaitannya dengan psikologi Nabi, atau dari teori kronologi yang dibangun berdasarkan urutan (sequence) gagasan keagamaan. Dengan membaca ulang teori kronologi yang ada, studi ini berargumen bahwa upaya rekonstruksi kronologi wahyu harus didasarkan pada bangunan sejarah dialektika Alquran dengan audiens pertamanya yang didukung oleh analisis linguistik. Studi ini melihat kronologi wahyu sebagai “drama ilahi” yang merefleksikan komunikasi dialektik antar berbagai aktor yang terangkum dalam teks yang kemudian diimani sebagai kalam Allah. Dengan demikian, studi ini menekankan bahwa dasar kronologi wahyu seharusnya merupakan rangkaian kejadian masa formasi Islam, sementara analisis terhadap gaya bahasa Alquran memainkan peran pendukung.